A Facile Synthesis and Drug Design of Some New Heterocyclic Compounds Incorporating Pyridine Moiety and Their Antimicrobial Evaluation - M. Abdelrazek, Fathy; M.Gomha, Sobhi; H. Abdelrahman, Aly; Metz, Peter; A. Sayed, Mohsen (Letters in Drug Design & Discovery, 2017)
Background: An efficient synthesis of hitherto unreported 4-heteroarylpyridines was described via regioselective 1,3-dipolar cycloaddition reactions of 3-(dimethylamino)-1-(pyridin-4- yl)prop-2-en-1-one (2) with nitrilimines 4a-h to afford the corresponding pyrazole derivatives 6a-h. Hydrazinolysis of 6a-c,e-f yielded the respective pyrazolopyridazines 7a-f. The enaminone 2 reacts also with 6-aminothiouracil (8) to yielded thione 9. The reaction of 9 with hydrazonoyl chlorides 3 yielded products 13a-h. Pyridine analogs substituted in the 4-position with a pyridinones 18, 20, 22 or naphthofuran 24 were also synthesized. The structures of the newly synthesized compounds were confirmed by spectral data and elemental analyses. Method: The newly synthesized products were evaluated for their antimicrobial activities. Results: The results revealed that compounds 18 and 24 have good activities compared with Cefepime reference drug. Moreover, the computational studies using MOE 2014.09 software are confirming the results in biological activity.
Keywords: enaminone